CONCEPTUAL APPROACHES TO STATE POLICY OF INTRODUCTION OF GENDER EQUALITY TO JUDICIAL SYSTEM - Orikhovska , N. (Theory and Practice of Public Administration, 2020)
A successful introduction of gender policy is one of the factors of implementing democratic reforms. Judicial power is a mandatory component of the mechanism of the state through which it performs its functions. The introduction of the principle of gender equality in the judicial system of Ukraine will contribute to the awareness of the social context of justice and the need for equal participation of women and men in making important decisions that have a significant impact not only on individuals but also on society as a whole. That is why it is necessary to apply conceptual approaches to the state policy of gender equality in the judicial system, which confirms the relevance of the topic of the article. Successful implementation of gender policy is possible if it is scientifically sound. There are various conceptual approaches to the state policy of introducing gender equality in the judicial system, in particular: – the concept of equal opportunities and justice. It takes into account the fact that women and men are equally qualified as judges and that there are no scientific or genetic qualities or characteristics that would justify the dominance of men in decision-making bodies; – the concept of democratic legitimacy. It stipulates that the composition of the judiciary should reflect the descriptive composition of society. Otherwise, justice will not be achieved and the trial and its outcome will lack legitimacy; – an approach to the unique contribution of women judges to the judicial activity. It relies on the justification of “gender differences”; – the utilitarian approach takes into account that women make up half of the population, and have the same skills, intelligence, experience and competencies, as male lawyers. Therefore, modern societies cannot afford to lose the intellectual strength and energy of half the population. The foreign experience of the EU member states testifies to successful achievement of gender parity in the judicial systems of these countries, the expansion of women’s representation in professional judicial positions due to application of a number of conceptual approaches in practice: anti-discrimination laws, directives and gender equality policy. In Ukraine, a conceptual approach is used, which contains the principle of equal rights and opportunities for women and men in access to judicial profession and participation in decision-making that affect not only the fate of individuals, but also the state and society as a whole. Sociological research suggests that this is not enough to achieve the desired result – elimination of traditional gender stereotypes, signs of gender discrimination in the professional environment of judges, and gender disparities in the judicial system of Ukraine. The application of the above conceptual approaches to the state policy of gender equality in the judicial system will help to take into account gender issues in state policy, as well as in strategies and programs of sustainable development related to the judicial system of Ukraine.